Pengaruh Kreativitas Guru Terhadap Hasil Belajar Siswa Di SMK Negeri 1 Lotu - Gulo, Arman Loys Kristian; Telaumbanua, Aprianus; Harefa, Envilwan Berkat; Telaumbanua, Arisman (Cetta: Jurnal Ilmu Pendidikan, 2024)
Education is essentially a process to develop students' potential comprehensively, including knowledge, skills, attitudes, and values. Teachers play a central role in the success of education, not only as deliverers of material but also as managers of learning. One of the important competencies that teachers must possess is creativity. Teacher creativity is defined as the ability to present new ideas, varied learning methods, and innovative strategies that are able to adapt to the needs of students. The goal of teacher creativity is to create learning that is interesting, motivating, and encourages optimal student learning outcomes. The research method used a quantitative approach with a descriptive design. The research subjects were 21 grade XII students majoring in Building Modeling and Information Design (DPIB). Data were obtained through questionnaires for the teacher creativity variable, and documentation for the learning outcome variable. The data analysis technique used simple linear regression. The results of the study showed a positive and significant influence between teacher creativity and student learning outcomes. The simple regression equation obtained was Ŷ = 43.093 + 0.497X, meaning that every one unit increase in teacher creativity increases learning outcomes by 0.497 points. Hypothesis test (thitung = 3.165 > ttabel = 2.072) with a significant value of 0.005 (<0.05) indicates that the alternative hypothesis is accepted. The coefficient of determination (R²) of 34.5% indicates that teacher creativity contributes to student learning outcomes, while the remaining 65.5% is influenced by other factors outside the study. In conclusion, teacher creativity plays a very important role in improving student learning outcomes, but other factors such as teaching quality, motivation, facilities and infrastructure, and the learning environment also need to be considered to achieve optimal learning outcomes.